Dynamic Imprinting of the Treg Cell-Specific Epigenetic Signature in Developing Thymic Regulatory T Cells - Herppich, Susanne; Toker, Aras; Pietzsch, Beate; Kitagawa, Yohko; Ohkura, Naganari; Miyao, Takahisa; Floess, Stefan; Hori, Shohei; Sakaguchi, Shimon; Huehn, Jochen (Frontiers in Immunology, 2019)
Regulatory T (Treg) cells mainly develop within the thymus and arise from CD25+Foxp3- (CD25+ TregP) or CD25-Foxp3+ (Foxp3+ TregP) Treg cell precursors resulting in Treg cells harboring distinct transcriptomic profiles and complementary T cell receptor repertoires. The stable and long-term expression of Foxp3 in Treg cells and their stable suppressive phenotype are controlled by the demethylation of Treg cell-specific epigenetic signature genes including an evolutionarily conserved CpG-rich element within the Foxp3 locus, the Treg-specific demethylated region (TSDR). Here we analyzed the dynamics of the imprinting of the Treg cell-specific epigenetic signature genes in thymic Treg cells. We could demonstrate that CD25+Foxp3+ Treg cells show a progressive demethylation of most signature genes during maturation within the thymus. Interestingly, a partial demethylation of several Treg cell-specific epigenetic signature genes was already observed in Foxp3+ TregP but not in CD25+ TregP. Furthermore, Foxp3+ TregP were very transient in nature and arose at a more mature developmental stage when compared to CD25+ TregP. When the two Treg cell precursors were cultured in presence of IL 2, a factor known to be critical for thymic Treg cell development, we observed a major impact of IL 2 on the demethylation of the TSDR with a more pronounced effect on Foxp3+ TregP. Together, these results suggest that the establishment of the Treg cell-specific hypomethylation pattern is a continuous process throughout thymic Treg cell development and that the two known Treg cell precursors display distinct dynamics for the imprinting of the Treg cell-specific epigenetic signature genes.